Carnation Creek watershed experiment—long‐term responses of coho salmon populations to historic forest practices. Issue 2 (18th January 2017) - Tschaplinski, Peter J.; Pike, Robin G.
Abstract: The Carnation Creek project is a long‐term study of the effects of forestry practices on a small coastal watershed (11 km 2 ) located in southwestern Vancouver Island. Initiated in 1970, this pretreatment versus post‐treatment case study consists of 5 years of preharvest, 6 years of during‐harvest, and now, 34 years of postharvest research. Forty‐one percent of the watershed was clearcut from 1976 to 1981. One tributary sub‐basin (1.1 km 2 ) was left as an unharvested reference drainage. Riparian treatments varied from clearcuts to a variable‐width buffer. Fish population responses to logging have been complex, and specific to species and life stages. Stream warming due partly to riparian harvest increased the growth and survival of juvenile coho salmon and elevated smolt production by 65% for nearly three decades. These relatively short‐term thermal benefits offset the effects of riparian clearcutting which included accelerated bank erosion, streambed scour, loss of stable in‐stream wood, and sediment movement downstream. Landslides in 1984 greatly amplified these effects but took more than 20 years to propagate downstream to reduce fish habitat complexity and increase streambed instability and sediment transport over the entire portion inhabited by anadromous salmon. These delayed impacts have surpassed the thermal‐related benefits for coho salmon. Fry‐to‐smolt overwinter survival has declined from a mean of 50% between 1982 and 2004 to 15% since 2005. Coho salmon smolt production has consequently been reduced to below prelogging levels. Results show that forestry‐related alterations may take decades to fully develop and persist for decades longer without watershed and stream channel restoration.